Effect of experimental Trypanosoma evansi on fertility in Black Bengal Buck - PRADHAN, SAKTIPADA; ROY, SEULI SAHA; MUKHOPADHYAYA, SUNIT KUMAR (The Indian Journal of Animal Sciences, 2013)
Healthy black Bengal bucks (12), about 12 month-old, of similar body weights (8.66±0.49) were acclimatized for 3weeks, and then divided into 2 groups – infected group (1; n=6) and non-infected control group (C; n=6). In theTrypanosoma evansi infected bucks mean semen volume (0.86±0.10 ml) and mean spermatozoal concentration (0.92±0.09 ×106mm3)) decreased significantly. Mean percentage of spermatozoal abnormalities (7.5±0.57) and mean percentage of dead spermatozoal count (32.60±3.50) increased significantly on 12th week post infection in infected buck. In control group mean semen volume and mean spermatozoal concentration slightly increased. Mean percentage of dead spermatozoa and spermatozoal abnormalities was invariable and no significant change was observed in control group throughout the experiment period. The tissue section of testes showed diffuse degeneration of spermatogonia and sertolicells, devoid of spermatozoa and proliferation of fibrous connective tissue in intertubular spaces. The testicular blood vessels in some places were infiltrated with inflammatory cells. The present study indicated antifertility effect of T. evansi in Black Bengal bucks.